Islamic Work Ethics in Indonesia Islamic Microfinance Institutions: A Bibliometric Review and Analysis - Christiyanto, Wenda Wahyu; Hadi Senen, Syamsul; Rofaida, Rofi (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
The concept of